2017
DOI: 10.1039/c6cc08716g
|View full text |Cite
|
Sign up to set email alerts
|

Development of molecularly imprinted polymers specific for blood antigens for application in antibody-free blood typing

Abstract: A novel system for blood type testing is developed based on the first molecularly imprinted nanoparticles specific to oligosaccharides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 12 publications
1
14
0
1
Order By: Relevance
“…After polymerization, the high‐affinity MIP nanoparticles were separated from the template through high temperature washing. The blood cell binding experiments showed that the optical density of blood type B was reduced by 19% as expected …”
Section: Biological Molecular Imprinting With Different Scalesupporting
confidence: 69%
See 2 more Smart Citations
“…After polymerization, the high‐affinity MIP nanoparticles were separated from the template through high temperature washing. The blood cell binding experiments showed that the optical density of blood type B was reduced by 19% as expected …”
Section: Biological Molecular Imprinting With Different Scalesupporting
confidence: 69%
“…Copyright 2015, Wiley‐VCH; B) schematics of the solid‐phase synthesis of MIP nanoparticles. Reproduced with permission . Copyright 2017, Royal Society of Chemistry.…”
Section: Biological Molecular Imprinting With Different Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Development of the displacement‐based assay . The experiments were conducted in microtiter plate wells modified with magnetic inserts as previously described ,. BSA‐treated BIONs (15.0 mg) were prepared as described above and added to a solution of aqueous, fluorescent, biotin‐specific nanoMIPs (2 mL, 0.83 mg mL −1 , 22 nM).…”
Section: Methodsmentioning
confidence: 99%
“…The internal opening of the disks allowed measurements of the reactions using standard microtiter plate readers. One of the examples of such application demonstrated that magnetic nanoMIPs imprinted with blood type B trisaccharide (Gal-α-1,3(Fuc-α-1,2)Gal) could be used in blood typing assays instead of natural antibodies [150]. The new format of the test system was based on magnetically-induced decolorization, caused by removal of erythrocytes from the solution by magnetic nanoMIPs (Figure 8).…”
Section: Nanomips In Assays and Sensorsmentioning
confidence: 99%